The necessity revealed by COVID-19 pandemic: Paradigm shift of Iran's healthcare system - Mohammadpour, Mohammadtaghi; Delavari, Sajad; Kavosi, Zahra; Peyravi, Mahmoudreza; Izadi, Reyhane; Bastani, Peivand (Frontiers in Public Health, 2023)
Background COVID-19 pandemic has resulted in drastic changes around the world, revealing vulnerable aspects of healthcare systems. This study aimed to explore how Iranian healthcare system experienced the paradigm shift during the pandemic and determine the aspects that need improvement during the pandemic era. Method This qualitative study was conducted in 2021. A framework analysis approach was used to analyze the content of the 19 semi-structured interviews with the healthcare system experts from Shiraz University of Medical Sciences (SUMS). The interviews‘ audio files changed into transcript after each session and data was saturated at the 19 interview. To increase the trustworthiness of the study, Guba and Lincoln's criteria including credibility, transferability, dependability, and confirmability were used. Goldsmith's five-step framework analysis was used applying MAX QDA version 10 software. Result Eight main themes and 20 subthemes were explored. The main themes included “strengthening the electronic health infrastructure,” “research for evidence-based decision making,” “dedicated financing to the pandemic,” “prevention of disruption in the effective provision of services and medicines,” “enriching the authority of the Ministry of Health by focusing on interactions,” “recruiting, managing and empowering health human resources with attention to financial and non-financial incentives,” “reforming educational approaches in training students in medical universities,” as well as “lessons learned from neglected aspects.” Conclusion To be ready to respond to a possible future pandemic and for a paradigm shift, bold steps must be taken to make fundamental changes in various aspects of the healthcare system including e-health development, evidence-based decision making, dedicated budgets for pandemics, reinforcement of interactions at the national and international level, as well as sufficient attention to healthcare workers from all financial, non-financial and educational aspects.